Development of Wordwall Media on Learning to Compare Object Weight in Grade 1 Elementary School - Ayu Syarifatunnisa (Universitas Pendidikan Indonesia (UPI), 2023)
The research was conducted based on conditions that occur in the field, where students find it difficult to learn mathematics, especially the material weighs objects. This causes students not to respond to educators' questions during question-and-answer activities. In addition, digital-based learning media for these materials are not yet available. Therefore, researchers developed digital-based learning media in the form of wordwalls. The purpose of the study is to describe the analysis of the needs of digital-based learning media, the design and development of wordwall media, the feasibility of wordwall media, and the response of educators and students to the wordwall media that has been developed. The study was conducted using the ADDIE method. Data collection through observation, interviews, document studies, expert validation, as well as the response of an educator and 32 students to the developed media. The results of the analysis showed that digital-based learning media was needed, media design was carried out through wordwall and then validated by 2 experts obtaining feasible criteria with a percentage of material expert validation of 90.62% and 87.5% validation of media experts so that the developed wordwall media could be used in learning. Then the results of the questionnaire of student responses to the developed media obtained 93.82% results with very practical criteria. Thus, wordwall media on the material comparing the weight of objects in grade 1 elementary school is valid and very practical to use.